The Effects of Transitional Care Program for Older Patients with Heart Failure during Coronavirus 2019 Pandemic - Mejunpet, ์Narumol; Nimit-Arnun, Nongpimol; Roojanavech, Sasitorn (NU Journal of Nursing and Health Sciences, 2023)
This study was a quasi-experimental research using the 2 groups, pre-test and post-test design. The purpose of this study was to compare the effects of a transitional care program for older patients with heart failure during Coronavirus 2019 pandemic. Participants were purposive sampling and, divided into 2 groups. The patients from the cardiology clinic were an experimental group, whereas those from and from outpatient department of medicine were in a comparison group, There were 35 patients in each group. The participants in experimental group received the 4-week program which consisted of face-to-face approach at an outpatient department and telemonitoring approach regarding self-care at home via phone and line application. Data collection consisted of demographic data questionnaires, physical function assessment, quality of life assessment, and readmission record. The content validity index was 1, the Cronbach’ a alpha coefficients of reliability were 0.95, 0.96, 0.92 and 0.95, Data were analyzed using descriptive statistics, t-test and z-test The results revealed that after the intervention, the patients in experimental group had significantly better score in physical function ability and, quality of life, whereas they had lower number of readmission than before and also in the comparison group.(p -value < .05) These findings showed that this program enhanced self-care behaviors in patients with heart failure. Nurses should implement this program for caring patients with heart failure during epidemic to provide continuing comprehensive healthcare service and improve patient’s quality of life.